Integrating technology planning with business planning - Metz, Philip D.
Philip D. Metz presents five "best practices" from a study by the Industrial Research Institute.
Five 'best practices' emerge from a two-year study of 50 companies.
A subcommittee of the Industrial Research Institute that has been studying the integration of R&D planning with business planning identified five "best practices" : 1) Establish a structured process for technology planning; 2) Foster active involvement between R&D and other functional areas within the organization; 3) Get top management commitment; 4) Organize for effective technology planning and buy-in by all functions; 5) Hold R&D and the business units accountable for measurable results.
Keywords: Technology planning; Business planning